Analysis of antimicrobial effects of a contactless, indirect cold atmospheric plasma-aerosol method for germ reduction on surfaces: an in vitro and in vivo study - Schaal, Tom; Schmelz, Ulrich; Hämmerle, Gilbert; Fuchs, Robert; Schorling, Timon; Kurras, Sandra; Koene, Marc; Tischendorf, Tim (Frontiers in Microbiology, 2025)
Cold Atmospheric Plasma-Aerosol (CAP-A) technology has emerged as a novel, contactless approach for antimicrobial treatment. This study evaluates the in vivo efficacy of CAP-A in reducing microbial contamination on human skin, building on obligatory in vitro testing. In vitro results demonstrated consistent 3–4.5 log unit microbial reductions across five standard organisms. In vivo evaluation using Escherichia coli revealed a mean log reduction factor of 4.77 (SD ± 0.44), exceeding the 4-log threshold considered clinically relevant. Notably, CAP-A showed comparable efficacy to an alcohol-based reference disinfection method (p = 0.134), without associated drawbacks such as thermal effects or ozone accumulation. Results suggest that CAP-A offers equivalent in vivo efficacy compared to previously documented CAP methods while minimizing tissue damage, thermal changes, and discomfort. The results underscore the potential of CAP-A as an effective and tolerable alternative to established CAP approaches, warranting further comparative research under standardized conditions. Future studies should examine both CAP and CAP-A technologies, broadening the spectrum of tested microorganisms, incorporating additional parameters, and rigorously assessing benefits and risks. This research could elucidate the underlying mechanisms driving differences in efficacy and side effect profiles, ultimately contributing to the optimization of plasma-based treatments in clinical and industrial settings.